THE ROLE OF MOVABLE GAMES IN EDUCATIONAL ACTIVITY OF JUNIOR SCHOOLCHILDREN - Poghosyan , L. H. (Modern Psychology, 2018)
In this article are expounded the theoretical ideas about the influence of the movable games, the educational activity of junior schoolchildren. Primary schoolchildren, especially first-class children, who are engaged in an educational process, face to physiological and psychological difficulties. Therefore, we put an aim to show, how the movable games influence on a children psycho-physiological health that directly affects on an educational activity, in wide sense of this concept.